Induction of resistance in tomato against Helicoverpa armigera (Hubner) using biofertilizers - V. Selvanarayanan, N. Muthukumaran (Recent Research in Science and Technology, 2009)
Based on preliminary and confirmatory field screening of 321 tomato accessions for resistance against fruit borer, Helicoverpa armigera (Hubner), a promising accession Varushanadu Local was selected for studying induction of resistance using biofertilizers viz., Azospirillum, Phosphobacteria, Pseudomonas and K-solubilizer. In comparison, a susceptible check, I979 was also evaluated. The feeding preference of H. armigera larva was the least towards Varushanadu Local than I979 irrespective of the biofertilizer. Among the biofertilizers K-solubilizer treated plants were the least preferred than others. A trend was observed in both the free choice and confinement tests.